CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) ON A COUPLE OF FERTILE AGE IN HOUSEHOLD ORDER RW 07RW 07 MEGA MARINA, PASIR PUTIH HOUSING COMPLEX, KOTO TANGAH DISTRICT, PADANG - Dwi Pratiwi Kasmara; Afrida Yelni; Yanti Yanti (PITIMAS: Journal of Community Engagement in Health, 2023)
Healthy conditions will be achieved if changing behavior from unhealthy to healthy behavior in order to create a healthy environment. Behavior is an individual's response to stimulation both from outside and from within him. PHBS (Clean and Healthy Living Behavior) is a set of behaviors that are practiced on the basis of awareness as a result of learning, which makes a person or family able to help themselves in the health sector and play an active role in realizing public health. Couples of Childbearing Age are married couples whose wives are between 15 and 49 years old or married couples whose wives are less than 15 years old and menstruating or whose wives are more than 50 years old, but still menstruating (menstruating). This activity was carried out by providing counseling about clean and healthy living behavior (PHBS) in RW 07 mega marina, white sand complex, Koto Tangah sub-district. The purpose of this activity is: to improve the quality of life of the elderly and the human development index (IPM). at RW 07 mega marina, white sand complex, Koto Tangah sub-district. Activity results: During the implementation of this community service activity, couples of childbearing age (PUS) have been able to carry out clean and healthy living behavior (PHBS). So that couples of childbearing age (EFA) are able to improve the quality of life and the human development index (IPM).